Modelling gerontechnology adoption within the framework of society 5.0 in Malaysia - Jumbri, Isma Addi; Aris, Nurin; Bakri, Mohammed Hariri (International Journal of Children, Women, The Elderly and Persons with Disabilities, 2022)
Gerontechnology is a new interdisciplinary academic and professional field combining gerontology and technology. Gerontology means the study of aging, and technology is the use of science to fulfil needs. Therefore, gerontechnology involves research and development techniques, technological products, services, and environments based on knowledge of aging processes. There are a lot of gerontechnology studies done, but the very little research focuses on exploring the influencing attributes that affect the users’ acceptance of gerontechnology. Thus, the objective of this conceptual paper is to propose a new model of the behavioural intention of gerontechnology adoption. This paper is then developed into research hypotheses for further studies. This research is expected to contribute significantly to the development of a new integrative adoption of the gerontechnology model in Malaysia en route to sustainable development. The significance of this research will also contribute to gerontechnology stakeholders, including the elderly, care professionals, managers within home care or social work organizations, technology designers and suppliers, and the government as the policymaker.